Birth Preparedness and Complication Readiness among Antenatal Women in a Tribal Area of a Central District, Kerala (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: antenatal women; birth preparedness; complication readiness; cross sectional study; tribal area